Perlindungan Hukum Bagi Pihak Yang Dirugikan Dalam Perjanjian Kerjasama Pembiayaan Biji Nikel - Hamada Reinaldy Mantulameten; Merry Tjoanda; Novyta Uktolseja (TATOHI: Jurnal Ilmu Hukum, 2023)
Introduction: This article analyzes the business cooperation agreement which in practice, the principle of balance is often ignored, so that when a default occurs, the creditor consortium cannot force the debtor to carry out its achievements through the execution of the debtor's assets as collateral, due to the lack of collateral provided by the debtor.Purposes of the Research: The purpose of this article is to find out the implementation of the financing cooperation agreement between PT Kingstone Anugerah Perkasa and PT Bumi Putera Abadi and PT Mineral Trobos, and to find out about legal protection for the aggrieved party in the financing cooperation agreement between PT Kingstone Anugerah Perkasa and PT Bumi Putera Abadi with PT Trobos Minerals. Methods of the Research: The research method used is normative juridical with a statutory approach conseptual approach and case approach, and uses secondary data and is analyzed qualitatively.Results of the Research: The financing cooperation agreement between PT Kingstone Anugrah Perkasa and PT Bumi Putera Abadi and PT Mineral Trobos did not go well. This is because in the post-contract/implementation phase of the agreed contents of the agreement, PT Mineral Trobos defaulted by not carrying out its obligation to complete the permit no later than 60 days from the signing of the financing cooperation agreement, so that PT Kingstone Anugrah Perkasa and PT Bumi Putera Abadi have the right to filed a lawsuit for default of PT Mineral Trobos to the Kendari District Court.